Structures, Stabilities and Electronic Properties of $MSn_{10} (M=Li, Be, B, Ca)$ (Journal of Atomic and Molecular Sciences, 2014)
The effect of impurity atoms on structures, stabilities and electronic propertiesof $MSn_{10} (M= Li, Be, B and Ca)$ clusters have been investigated using the densityfunctional theory based B3LYP method with cc-pVTZ(-PP) basis set. The results showthat the location of the impurity atom depends on the interactions of impurity atomswith the host cluster and the size of the impurity atom itself. The stability has been analyzedbased on average binding energy, vertical ionization potential, vertical electronaffinity, HOMO - LUMO energy gap and embedding energy. Several clusters, such as $BeSn_{10},$ $Sn_{10}$ and $Sn^{(2-)}_{10}$ with enhanced stability have been identified. The stability of $Sn_{10}(C_{3v})$ can be rationalized using the jellium shell model. Molecular orbital analysesreveal that the enhanced stability of $BeSn_{10}$ and $Sn^{(2-)}_{10} (D_{4d})$ with 42 valence electronsmay arise from a crystal-field splitting of the 1G shell and from the closed-shell natureof the $π$ subsystem, which is subjected to the $2(N_{π}+1)^2$ rule with $N_{π}=1.$ Both $BeSn_{10}$ and $Sn^{(2-)}_{10}$ clusters can be considered to be aromaticity with $8π$ electrons, further confirmedby the large nucleus-independent chemical shift values.